From Narcissus to Epicurus: the emergence and preservation of individuality - SPINELLI, MIGUEL (2011)
This paper aims to analyze the theme of individuality as it is presented in the myth of Narcissus and in Epicurus. The discovery of individuality is seen here to be the result of an experience of self understood as a consciousness of self. The Narcissus myth is analyzed as a dramatization of that personal discovery; in Epicurus, individuality is reached through self-instruction and the concept of autarkhéia.